2002
DOI: 10.1128/iai.70.8.4571-4580.2002
|View full text |Cite
|
Sign up to set email alerts
|

Opsonization Modulates Rac-1 Activation during Cell Entry byLeishmania amazonensis

Abstract: Lesions caused by Leishmania amazonensis normally heal, but relapses occur due to parasite persistence in host tissues. It has been proposed that infection of fibroblasts plays an important role in this process by providing the parasites with a safe haven in which to replicate. However, most previous studies have focused on the entry of Leishmania into macrophages, a process mediated by serum opsonins. To gain insight into a possible role of nonopsonic entry in the intracellular persistence of amastigotes, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
31
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 58 publications
6
31
0
2
Order By: Relevance
“…Consistent with these findings, we previously showed that uptake of serum-opsonized L. donovani promastigotes by macrophages is dependent on RhoA, whereas Rac1 and Cdc42 mediate the internalization of unopsonized promastigotes [22]. In the case of amastigotes, the only information available was obtained using CHO cells infected with axenic L. amazonensis amastigotes, which revealed a phagocytic pathway apparently distinct from either types I or II [23]. Hence, entry of amastigotes in CHO cells involved Rho and Cdc42 but not Rac1.…”
Section: Introductionsupporting
confidence: 51%
See 2 more Smart Citations
“…Consistent with these findings, we previously showed that uptake of serum-opsonized L. donovani promastigotes by macrophages is dependent on RhoA, whereas Rac1 and Cdc42 mediate the internalization of unopsonized promastigotes [22]. In the case of amastigotes, the only information available was obtained using CHO cells infected with axenic L. amazonensis amastigotes, which revealed a phagocytic pathway apparently distinct from either types I or II [23]. Hence, entry of amastigotes in CHO cells involved Rho and Cdc42 but not Rac1.…”
Section: Introductionsupporting
confidence: 51%
“…Accordingly, we show that Arf6 is needed for efficient amastigote entry in macrophages. Morehead and colleagues [23] studied the role of Rho-family GTPases in the entry of axenic L. amazonensis amastigotes in CHO cells. They found that nonopsonic entry required Cdc42 and Rho, whereas entry of amastigotes opsonized with either fibronectin or IgG was mediated by Rac1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Promastigotes interact with multiple receptors, like the complement receptor CR3 (Russell and Wright, 1988); binding is enhanced by complement component fragment C3bi opsonization mediated by lipophosphoglycan (LPG) (Mosser et al, 1992;Puentes et al, 1988). The FcR subclass FcγR, which is required for IgG-mediated phagocytosis, is primarily responsible for amastigote uptake (Guy and Belosevic, 1993;Kima et al, 2000;Woelbing et al, 2006), and IgG opsonization of amastigotes facilitates these interactions (Morehead et al, 2002). Leishmania receptor binding causes actin-rich phagocytic cups to engulf the parasite (Lodge and Descoteaux, 2008); however, the signaling process directing cup formation is not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen bonding [13], electrostatic interactions [14], specific interactions between surface proteins and extracellular matrix proteins [11,15,16], and shear forces [17] all have been shown to mediate bacterial adhesion. GBS will only adhere to adsorbed Fn, not soluble Fn1, 18,19; this behavior helps GBS evade the host immune system since soluble Fn acts as an opsonin [20]. The mechanism for specific binding of GBS to immobilized Fn is unknown, but one hypothesis is that the adsorbed Fn undergoes conformational changes to reveal cryptic binding sites [19].…”
Section: Introductionmentioning
confidence: 99%